Insights from students' writing of literature review via online writing clinic with e-tutors on google docs - Ng, Siew Fong (2016)
Previous studies have lent credence to the fact that wiki has been widely used as a platform for teaching and learning. Google Docs is considered to be a distinguished platform because it enables both synchronous and asynchronous modes of communication as well as offline usage. Given the various benefits offered by Google Docs, the present study aims at: i) examining the e-tutors’ pedagogical practices in tutoring students writing the literature review via Google Docs; ii) clarifying the e-tutors’ prominent evaluation criteria in tutoring students writing literature review via Google Docs; and iii) determining the effects of e-tutoring via Google Docs. The participants of the study consists of three e-tutors and four students. In employing qualitative approach, the data collection methods of the study comprise virtual observation, documents such as writing draft and students’ journal entries as well as interview with both the students and e-tutors. Content analysis was employed when analyzing the data. Findings emanated from the study revealed that the e-tutors had engaged in some pedagogical practices such as frequent use of direct feedback, playing a dominant role, pointing out the strengths and weaknesses of the students, and providing metalinguistic feedback. Besides, the e-tutors also adhered to some prominent evaluation criteria, namely: i) expansion of pertinent subject matter, ii) inclusion of citation, iii) coherence and cohesion, iv) language usage, as well as v) organization. Apart from that, the effects of e-tutoring via Google Docs on students’ writing encompass awareness on the gravity of plagiarism, emulating expert writers’ writing practice, acknowledging the importance of planning prior to writing, revising their own work, addressing the significance of coherence, properly organizing ideas/points and performing wide readings. From the findings, it is implied that the e-tutors had taken into account some factors when tutoring the students. The factors include audience factor, task factor, and objectives of the task. Moreover, the e-tutors’ adherence to certain prominent evaluation criteria highlights the salient features that constitute a good quality of literature review. Thus, the features should be considered when evaluating novice student writers’ literature review. A working framework for online writing clinic is derived from the findings.